Some analytical models of anisotropic strange stars - Murad, Mohammad Hassan (© Springer Science+Business Media Dordrecht 2015, 2016)
This article was published in the Astrophysics and Space Science [© Springer Science+Business Media Dordrecht 2015] and the definite version is available at : http://10.1007/s10509-015-2582-2 The Journal's website is at: http://link.springer.com/article/10.1007/s10509-015-2582-2